1972
DOI: 10.1139/p72-326
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Concentrations in Supersonic Free Jets

Abstract: Measurements have been made of the concentration of dimers produced during the expansion from a supersonic nozzle. The gases studied were: Ar, N2,O2, CO, CO2, C2H4, and N2O. It is shown that an effective specific heat ratio of the expanding gas offers a means of correlating the dimer concentration in terms of the source gas pressure and temperature. The two nozzles employed had opening diameters of 0.14 mm and 0.065 mm. An attempt to obtain a universal dependence for all gases in terms of reduced source parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1974
1974
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For the other extreme case q = 1, the terminal dimer mole fraction is dominated by dimer formation during the free-jet expansion and the initial concentration of dimers is negligible. The available data for terminal dimer concentrations in free-jet expansions of rare gases 28,29,71,72 are correlated satisfactorily by q = 0.4 ͑Refs. 33 and 34͒ indicating that both thermodynamics and kinetics play a role.…”
Section: A Dimer Formationmentioning
confidence: 81%
See 1 more Smart Citation
“…For the other extreme case q = 1, the terminal dimer mole fraction is dominated by dimer formation during the free-jet expansion and the initial concentration of dimers is negligible. The available data for terminal dimer concentrations in free-jet expansions of rare gases 28,29,71,72 are correlated satisfactorily by q = 0.4 ͑Refs. 33 and 34͒ indicating that both thermodynamics and kinetics play a role.…”
Section: A Dimer Formationmentioning
confidence: 81%
“…25 and 26͒ clusters has also been investigated. Several criteria have been developed for correlating the onset of condensation 27,28 and several nucleation models have been proposed which provide empirical estimates of terminal cluster concentrations for specific cases. 3,6,[29][30][31][32] Hagena and Obert 31 were the first to develop scaling laws to predict the onset of clustering and for correlating the size of the clusters.…”
Section: Introductionmentioning
confidence: 99%
“…(3) becomes Vo-< K . /A *> < Na6> (4) where <Na^ > is the expectation value of the product. One notes from Eq.…”
Section: Rayleigh Scatteringmentioning
confidence: 99%
“…Several criteria were developed for correlating the onset of condensation [208,209] and different nucleation models have been proposed which provide empirical estimates of dimer concentrations for specific cases [210,211]. Gordon et al adapted a recombination model suggested by Bunker in order to predict terminal dimer concentrations [3].…”
Section: Cluster Formation In N-d 2 Beamsmentioning
confidence: 99%